La gestión empresarial y la comercialización en el comercial raza en Riobamba - Tituaña Ramirez, Nataly Jajaira (2024)
ABSTRACT: This research examines the management and marketing processes of Comercial Raza, aprominent company in Riobamba known for its natural products. Despite its historical significance, the company faces challenges such as high staff turnover, logistical deficiencies, and inadequate marketing strategies, impacting its market position. Human resources management lacks continuity and stability, resulting in frequent recruitment and training costs, affecting customer service. Logistics processes fail to ensure timely supply and product quality due to procedural gap. Weak brand positioning and promotion strategies further hamper the company's potential. The research aims to assess how these management issues affect Comercial Raza's commercial performance and proposes solutions. The study employs a hypothetical-deductive methodology with descriptive, explanatory, and field designs, using consumer surveys and manager interviews for data collection. Findings confirm the identified deficiencies, linking inadequate management to decreased sales, market share, and profitability. Proposed solutions include staff incentive plans, improved distribution systems, digital marketing strategies, and brand positioning efforts. Implementation of these strategies is expected to restore Comercial Raza's market leadership, enhance customer satisfaction, and bolster competitiveness.